Valores de referência geoquímicos do solo nos estados do Piauí e Maranhão: a nova fronteira agrícola brasileira - Santos, Jefferson Nunes dos (2017)
The establishment of geochemical reference values (GRVs) is necessary for the determination of the actual state of soil and sediment contamination to avoid subjective and unreliable risk assessments. The Parnaíba River Basin is emerging as one of Brazil’s agricultural frontiers. The objective of this study is to establish GRVs for the Upper Parnaíba River Basin via an integrated method using direct and indirect soil analyses. The predominant soil in the region is yellow latosol. Soil samples were collected in permanent preservation areas along the Parnaíba River. The amounts of Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, Pb and Zn in the soil samples were measured using flame atomic absorption spectrometry. The concentrations of the elements in the soil of the Parnaíba River Basin follow the sequence Fe > K > Mg > Na > Mn > Ca > Zn > Pb > Cu> Ni > Co > Cr > Cd. The soil chemical element concentration data were not normally distributed nor independent; therefore, it was appropriate to apply non-parametric statistical methods based on the third quartile to establish the GRVs.